INSIGHTS ON FORESTS USE IN COMMUNES AFTER THE COLLAPSE OF SOCIALISM IN ALBANIA - Laze, Kuenda (European Scientific Journal, ESJ, 2014)
This study examines forest use in post-socialist Albania. The aim was to investigate the use of high-stem forests, coppice forests, broadleaved forests and coniferous forests for resource and biodiversity in commune forests. Data of presences and absences of high-stem forests, coppice forests, broadleaved forests and coniferous forests were measured from forest surveys of management plans. These data were integrated with environmental, socioeconomic and policy data using generalized linear models and spatial scale. Policy models had ten neighborhood variables of the density of roads and the density of human settlements from one km to five km with a priory assumption that the extent of these variables influenced the use of forests in post-socialist Albania. The final policy model of commune forests included accessibility variables and had a prediction accuracy of 99 percent at radii of 2 km for high-stem forests and 1 km for coppice forests and broadleaved forests. It is recommended the implementation of a policy to use sustainably all forests in Albania.